Mode of infant feeding, eating behaviour and anthropometry in infants at 6-months of age born to obese women - a secondary analysis of the UPBEAT trial - Nashita Patel; Kathryn V. Dalrymple; Annette L. Briley; Dharmintra Pasupathy; Paul T. Seed; Angela C. Flynn; Lucilla Poston; on behalf of the UPBEAT Consortium (BMC, 2018)
Abstract Background Maternal obesity and rapid infant weight gain have been associated with increased risk of obesity in childhood. Breastfeeding is suggested to be protective against childhood obesity, but no previous study has addressed the potential benefit of breastfeeding as a preventive method of childhood obesity amongst obese women. The primary aim of this study was to assess the relationship between mode of feeding and body composition, growth and eating behaviours in 6-month-old infants of obese women who participated in UPBEAT; a multi-centre randomised controlled trial comparing a lifestyle intervention of diet and physical activity to standard care during pregnancy. Methods Three hundred and fifty-three mother and infant pairs attended a 6-months postpartum follow-up visit, during which they completed the Baby-Eating Behaviour Questionnaire, a parent-reported psychometric measure of appetite traits. Measures of infant body composition were also undertaken. As there was no effect of the antenatal intervention on infant feeding and appetite the study was treated as a cohort. Using regression analyses, we examined relationships between: 1) mode of feeding and body composition and growth; 2) mode of feeding and eating behaviour and 3) eating behaviour and body composition. Results Formula fed infants of obese women in comparison to those exclusively breastfed, demonstrated higher weight z-scores (mean difference 0.26; 95% confidence interval 0.01 to 0.52), higher rate of weight gain (0.04; 0.00 to 0.07) and greater catch-up growth (2.48; 1.31 to 4.71). There was also a lower enjoyment of food (p = 0.002) amongst formula fed infants, following adjustment for confounders. Independent of the mode of feeding, a measure of infant appetite was associated with sum of skinfold thicknesses (β 0.66; 95% CI 0.12 to 1.21), calculated body fat percentage (0.83; 0.15 to 1.52), weight z-scores (0.21; 0.06 to 0.36) and catch-up growth (odds ratio 1.98; 1.21 to 3.21). Conclusions In obese women, exclusive breastfeeding was protective against increasing weight z-scores and trajectories of weight gain in their 6-month old infants. Measures of general appetite in early infancy were associated with measures of adiposity, weight and catch up growth independent of cord blood leptin concentrations and mode of early feeding.